Molecular dynamics simulations of Hydrogenobacter thermophilus cytochrome c552: comparisons of the wild-type protein, a b-type variant, and the apo state. - Smith, L; Davies, R; van Gunsteren, W (2006)
Molecular dynamic simulations have been performed for wild-type Hydrogenobacter thermophilus cytochrome c(552), a b-type variant of the protein, and the apo state with the heme prosthetic group removed. In the b-type variant, Cys 10 and Cys 13 were mutated to alanine residues, and so the heme group was no longer covalently bound to the protein. Two 8-ns simulations have been performed for each system at 298 and 360 K. The simulations of the wild-type protein at 298 K show a very close agreement with experimental NMR data. A fluxional process involving the side chain of Met 59, which coordinates to the heme iron, is observed in accord with proposals from NMR studies. Overall, the structure and dynamical behavior of the protein during the simulations of the b-type variant is closely similar to that of the wild-type protein. However, side chains in the heme-binding site show larger fluctuations in the b-type variant simulation at 360 K. In addition, structural changes are seen for a number of residues close to the heme group, particularly Gly 22 and Ser 51. The simulations of the apo state show significant conformational changes for residues 50-59. These residues form a loop region, which packs over the heme group in the wild-type protein and hydrogen bonds to the heme propionate groups. In the absence of heme, in the apo state simulations, these residues form short but persistent regions of beta-sheet secondary structure. These could provide nucleation sites for the conversion to amyloid fibrils.